Challenges of Dispute Settlement through International Court of Justice (ICJ): the Case of Ukraine v. Russian Federation the Decision on Provisional Measures on Alleged Violation of Genocide Convention - Bezabh Abebe Bahiru (European Scientific Journal, ESJ, 2022)
This article aims to study the challenges faced by the ICJ in the international dispute resolution processes by analyzing the case between Ukraine v. Russia emphasizing the decision of the court on claims of provisional measures to stop Russian military operation in Ukraine. The qualitative approach was utilized in this research referring to both primary and secondary sources. The finding shows that ICJ has been facing challenges which is revealed in Ukraine’s case too. Regardless of the marvelous efforts of ICJ, state parties are quitting the jurisdiction of ICJ by rejecting the principle of international law of treaties. Besides, the gap in institutional independence in the process of election of judges has involved the veto power of the Security Council which is a political organ. Even more, the election of ad hoc judges is based on the intention of national representation. To this effect, the verdict on Ukraine’s claim has been decided by the split majority vote and judges’ individual independence in decision-making has been influenced by national interest, the political orientation of judges, ideology, and, diplomatic relations of states. The worst is that the judgment enforcement UN Security Council’s structural posture caused failure to execute decisions. Favoritism and intervention by unilateral sanction are also other problems. Therefore, the writer suggests the court demand a radical change to attain its intended object.